Nuances in component nasal hump reduction - Sadick, Haneen; Rowe-Jones, Julian M.; Gassner, Holger G. (Journal of plastic, reconstructive & aesthetic surgery, 2018)
Importance - Nasal hump reduction is a frequent manoeuvre in rhinoplasty. Over the last years, composite hump reduction has been advocated in favour of component hump reduction. The latter allows a more controlled and stepwise approach in reducing the nasal dorsum by deprojecting the cartilaginous dorsum separately from the bony dorsum. This approach also preserves the upper lateral cartilages (ULCs) and their mucosa. - Objective - To analyse the intricacies of the anatomic transition zone between the ULCs, the rhinion and the nasal bones as they pertain to component hump reduction. - Method - Anatomical dissections with five fresh cadaveric heads were performed in this study. The cephalic extension of the ULCs beneath the nasal bones was modified and measured after component hump reduction on both sides of the rhinion. - Results - Central detachment of the ULCs from the bony dorsum and their release from the medial undersurface of the nasal bones allows for complete preservation of the ULCs. This is achieved by inferior-medial rotation of the cephalic ends of the ULCs against the septum. If not released completely during hump reduction, a substantial loss of the ULCs may be the consequence. - Conclusions - The described manoeuvre allows the preservation of the cephalic components of the ULCs underneath the bony dorsum during component hump reduction. The result is a smoother transition line at the keystone area and along the entire bony-cartilaginous dorsum with a straighter aesthetic dorsal profile and oblique view. The present findings allowed us to present an operative algorithm with implementation into clinical practice.
Gesehen am 04.05.2020